Verapamil treatment after coronary angioplasty in patients at high risk of recurrent stenosis. Issue 3 (March 1994) - Hoberg, E.; Dietz, R.; Frees, U.; Katus, H. A.; Rauch, B.; Schömig, A.; Schuler, G.; Schwarz, F.; Tillmanns, H.; Niebauer, J.
Abstract : OBJECTIVE–To evaluate the efficacy of high-dose verapamil treatment (240 mg twice daily) in the prevention of angiographic restenosis after primary successful coronary angioplasty in patients at high risk of recurrent obstruction. DESIGN–A placebo controlled, double blind trial in which patients with stable angina pectoris and patients with unstable angina or non-Q wave infarction treated with 330 mg aspirin and 75 mg dipyridamole twice daily were randomised to a verapamil group or a control group. Follow up angiography was performed 6 months after angioplasty or sooner if signs of recurrent ischaemia developed. SETTING–University department of cardiology. PATIENTS–196 consecutive patients undergoing coronary angioplasty from the beginning of April 1987 to the end of March 1989 and meeting the selection criteria that included the presence of at least one of six predefined risk factors for restenosis. At the time of coronary angioplasty 113 patients had unstable angina or non-Q wave infarction and 83 had stable angina pectoris. RESULTS–In 89 (91%) patients in the verapamil group and in 83 (85%) control patients follow up angiograms were available. The restenosis rate was lower in the verapamil group (48.3%) than in the placebo group (62.7%) (odds ratio 0.56, 95% confidence interval (CI) 0.303 to 1.025 p = 0.059). Of the 172 patients in whom follow up angiograms were available, 24 (13 taking verapamil and 11 taking placebo) did not comply with the trial for more than 40 (34) days (mean (1 SD)). For the remaining 148 patients the restenosis rate was 47.4% in the verapamil group and 63.9% in the placebo group (odds ratio 0.52, 95% CI 0.271 to 0.993, p = 0.046). In the 97 patients with unstable angina or non-Q wave infarction the restenosis rate was not significantly influenced by verapamil (55.8% with verapamil v 62.2% with placebo, odds ratio 0.77, 95% CI 0.339 to 1.728, p = 0.520). In the 75 patients with stable angina pectoris the restenosis rate dropped from 63.2% with placebo to 37.8% with verapamil (odds ratio 0.36, 95% CI 0.137 to 0.917, p = 0.038). CONCLUSION–The observed beneficial effect of high-dose verapamil treatment on the angiographic restenosis rate in patients with stable angina pectoris and at increased risk of recurrent obstruction requires confirmation in further prospective studies.